Organic flash memory on various flexible substrates for foldable and disposable electronics - Lee, Seungwon (Nat Commun, 2017)
With the emergence of wearable or disposable electronics, there grows a demand for a flash memory realizable on various flexible substrates. Nevertheless, it has been challenging to develop a flash memory that simultaneously exhibits a significant level of flexibility and performance. This is mainly due to the scarcity of flexible dielectric materials with insulating properties sufficient for a flash memory, which involves dual dielectric layers, respectively, responsible for tunneling and blocking of charges. Here we report ultra-flexible organic flash memories based on polymer dielectrics prepared by initiated chemical vapor deposition. Using their near-ideal dielectric characteristics, we demonstrate flash memories bendable down to a radius of 300 μm that exhibits a relatively long-projected retention with a programming voltage on par with the present industrial standards. The proposed memory technology is then applied to non-conventional substrates, such as papers, to demonstrate its feasibility in a wide range of applications.